Development of the bamboo forest economy: Reviewing China's 'bamboo as a substitute for plastic initiative' and its development - Yanyi Li; Nan Wang; Abdul Rais Abdul Latiff (Advances in Bamboo Science)
Plastic pollution has emerged as a major environmental concern, posing a significant threat to ecosystems and human health. The necessity for alternatives is becoming increasingly apparent. This study uses China's 'bamboo as a substitute for plastic initiative' as a point of departure for an investigation of its impact on the development of the bamboo forest economy. The properties of bamboo, including its sustainability, biodegradability and high carbon fixation rate, make it a potential substitute for plastic. We examine the dynamics of the bamboo industry in a number of countries including Nigeria, Nepal, Ethiopia, Japan and India, examining its applications and challenges in diverse cultural and social contexts. We focus on the present status of the implementation of the 'bamboo as a substitute for plastic initiative' in China and assess its efficacy in reducing reliance on plastic and advancing the sustainable development of the bamboo forest economy. We identify several challenges facing China's bamboo industry, including an incomplete industrial chain, high development costs and low mechanisation, and present specific policy recommendations designed to facilitate the sustainable advancement of the bamboo forest economy. We offer academic support for a more profound comprehension and advancement of bamboo as a potential substitute for plastic, as well as strategic insights for global environmental protection, combating climate change, and the promotion of a green economy.